2018
DOI: 10.1007/s00380-018-1315-1
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific characteristics of vascular cell adhesion molecule-1 levels in patients with peripheral artery disease

Abstract: Peripheral arterial disease (PAD) is one of the most common manifestations of systemic atherosclerosis. The prevalence of unrecognized PAD is high, leading to a lack of opportunity to detect subjects at a high risk for cardiovascular events. Inflammatory processes play an important role in the disease initiation as well as in the disease progression. Vascular cell adhesion molecule 1 (VCAM-1), a biomarker of endothelial dysfunction, appears to be an important mediator in inflammatory processes. Therefore, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Under steady-state conditions, the expression levels of VCAM-1 and ICAM-1 are usually low. It has been reported that down-regulated expression of VCAM-1 and ICAM-1 could protect against disruption of BBB [20,21,51]. Findings from the current study showed that ICAM-1 and VCAM-1 were transcriptionally upregulated in the brain of 1,2-DCE-intoxicated mice through the p38 MAPK/ NF-κB signaling pathway, and also being induced by IL-1β.…”
Section: Discussionsupporting
confidence: 49%
“…Under steady-state conditions, the expression levels of VCAM-1 and ICAM-1 are usually low. It has been reported that down-regulated expression of VCAM-1 and ICAM-1 could protect against disruption of BBB [20,21,51]. Findings from the current study showed that ICAM-1 and VCAM-1 were transcriptionally upregulated in the brain of 1,2-DCE-intoxicated mice through the p38 MAPK/ NF-κB signaling pathway, and also being induced by IL-1β.…”
Section: Discussionsupporting
confidence: 49%
“…VCAM-1 belongs to the immunoglobulin superfamily and can be expressed in endothelial cells, smooth muscle cells, and macrophages 38 . Some previous studies have observed an early increase in VCAM-1 levels within 6 h of injury, thus implying that VCAM-1 plays a role in early vascular inflammation and that the early application of a VCAM-1 antibody could inhibit the development of intimal hyperplasia 39 . Our results demonstrated that BSP inhibited early intimal hyperplasia and inflammation by inhibiting the production of VCAM-1.…”
Section: Discussionmentioning
confidence: 90%
“…Not only high plasm glucose, lipid and high blood pressure, but also aging itself can cause arterial stiffness. 14 15,16 However, we found the serum VCAM levels of hypertensive patients were lower than normotensive participants. In previous published study, serum VCAM levels were not found to be elevated in pulmonary hypertension or gestational hypertension, and low VCAM level might lead to fetal growth restriction.…”
Section: Bio-markers For Predicting Arterial Stiffness In Regressionmentioning
confidence: 54%